A Study on successful experience and sustainable development of Chinese women's gymnastics performance - Taking the gymnastics games in last five Olympic Games for instance - Long, B.; Li, J. (Proceedings of the 2017 2nd International Conference on Politics, Economics and Law (ICPEL 2017), 2018)
Taking the gymnastics games in last five Olympic Games (27th-31th) for instance, this paper uses the methods of literature consultation and mathematical statistics to study the successful experience and sustainable development of Chinese women's gymnastics performance and to summarize the new trends of women's gymnastics games in last five Olympic Games by comparing with the rivals of Chinese women's gymnastics in order to provide a theoretical basis and practical value for the further development of Chinese women's gymnastics.